Kontakty sportowe PRL-NRD ze szczególnym uwzględnieniem współpracy przygranicznej = Socio-cultural cooperation on the German-Polish borderland with the particular emphasis on sporting relations - Godlewski, Piotr (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Cooperation in sports between Poland and GDR was the cooperation of two totalitarian countries, which made this realm of social life an important tool in domestic and international politics. Sport was to play an important role in propaganda, showing the progress in this field as a significant factor of civilization development. Moreover, in GDR it was used as one of the main factors shaping the GDR`s national identity in the international arena.
Keywords: sport; PRL; NRD; stosunki polsko-niemieckie; pogranicze polsko-niemieckie